Analysis of the degradation in the Wells turbine blades of the Pico oscillating-water-column wave energy plant. (November 2019) - Bruschi, D.L.; Fernandes, J.C.S.; Falcão, A.F.O.; Bergmann, C.P.
Abstract: This paper presents an analysis of the degradation occurring in the air turbine blades of a oscillating-water-column wave energy converter, more precisely that of the Pico Power Plant. This plant is recognized as a real-scale infrastructure responsible for transforming wave energy into electricity and connected to the distribution grid. The study involves the analysis of the material used in the manufacture of the turbine and presents results on the effects of corrosion during the 19 years of Pico Power Plant operation. Highlights: Historical and technical overview of the Pico OWC plant. Technical details of the Wells turbine at Pico Power Plant, with special focus on the construction materials. Degradation mechanisms of the Wells turbine of Pico Power Plant reveal a synergic effect of wear and pitting corrosion. New materials are suggested for OWC turbines in aggressive environments, with improved resistance to both wear and corrosion.